Institutional Trading Frictions - CHIYACHANTANA, Chiraphol New (Institutional Knowledge at Singapore Management University, 2009)
We propose and empirically examine a comprehensive measure of institutional trading frictions to include the dimensions of price impact, quantity of execution, return dynamics, speed of execution or order splitting, and trading commissions. Our empirical analysis reveals that various hidden components of institutional trading frictions such as adverse selection and clean-up costs are persistent and could add significantly to previously measured directly observable components of transaction costs. Our simultaneous system of equations accounts for the endogeniety in institutional order aggressiveness based on potentially superior information as well as order splitting strategies in the implementation stage to reduce transaction costs. Order aggressiveness, market conditions and other stock characteristics are associated with significant variations in trading frictions.